Self-Efficacy as a Behavioral Enabler of Self-Care in Chronic Heart Failure - Tobi Pitora; Helza Risdianti; Dzikra Fitria Amita; Aurellia Firstania; Dinda Nur Fajri Hidayati Bunga; Annisa Pratiwi Gunawan; Yusuf Hanafiah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Chronic heart failure (CHF) is a major health problem associated with morbidity, repeated hospitalization, and long-term self-management demands. Although self-care is essential for symptom control and prevention of deterioration, many patients have difficulty maintaining effective daily management. Self-efficacy is considered an important psychological factor that may support self-care behavior.. Objective: This study aimed to examine the relationship between self-efficacy and self-care among patients with chronic heart failure and to contextualize the role of self-efficacy in supporting self-management behavior. Methods: A cross-sectional study was conducted involving 74 patients with CHF. Data were collected using the Self-Care of Heart Failure Index (SCHFI) v.6.2 and the General Self-Efficacy (GSE) Scale. Data were analyzed using descriptive statistics, Pearson’s correlation, independent t-test, and multiple linear regression. Results: Most participants were male (70.3%), with a mean age of 52.01 ± 13.46 years. The mean self-efficacy score was 35.00 ± 3.75, and the mean self-care score was 69.66 ± 3.80. Self-efficacy was positively correlated with self-care (r = 0.343, p = 0.003) and remained a significant predictor in multivariate analysis (β = 0.31, p = 0.004). Conclusion: Self-efficacy was positively associated with self-care among patients with chronic heart failure, but the modest strength of the relationship suggests that self-care is shaped by multiple interacting factors. These findings support the view that self-efficacy functions as a behavioral enabler rather than a standalone determinant of self-care. Interventions aimed at improving CHF self-management should therefore combine confidence-building strategies with broader educational, clinical, and contextual support